Unusual cetacean stranding events of Taiwan in 2004 and 2005 - Wang , John Y.; Yang , Shih-Chu (J. Cetacean Res. Manage., 2023)
In early 2004 and in 2005, several unusual stranding events occurred in Taiwan during a period when large-scale naval exercises were conducted in and on nearby waters. Gross examination of the partial remains of two carcasses (a ginkgo-toothed beaked whale (Mesoplodon ginkgodens) and a pygmy killer whale (Feresa attenuata)) and an intact Risso’s dolphin (Grampus griseus) revealed that the former two had internal injuries to structures associated with or related to acoustics or diving. The several unusual stranding events and the findings of the gross post mortem examination of the only specimens that were available for study were suggestive that nearby naval exercises may have contributed to or caused the death of at least one cetacean in this region and that species other than beaked whales may also be susceptible to such activities. With an increasing number of military exercises in this region, more attention to the impacts of such activities on cetaceans is needed.